Pengaruh Komunitas Belajar Guru, Kolaborasi Guru, dan Komunikasi Interpersonal terhadap Kualitas Pengajaran pada SMP Negeri di Kecamatan Ngombol - Maulani, Rina; Rejokirono, Rejokirono; Supriadi, Didi (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to: (1) describe the condition of teacher learning communities, teacher collaboration, interpersonal communication, and teaching quality, and (2) analyze the influence of these three variables on teaching quality among junior high school teachers in Ngombol District. A quantitative descriptive approach was employed, with simple linear regression used to examine the effect of each independent variable (X₁, X₂, X₃) on the dependent variable (Y), and multiple linear regression applied to test the simultaneous effects. The findings reveal that: (1) all variables were categorized as very high; (2) teacher learning communities had a positive and significant effect on teaching quality (t = 5.396; p < 0.001); (3) teacher collaboration had a positive and significant effect on teaching quality (t = 4.907; p < 0.001); (4) interpersonal communication had a positive and significant effect on teaching quality (t = 4.806; p < 0.001); and (5) the three independent variables collectively exerted a positive and significant influence on teaching quality (F = 21.334; p < 0.001). These results highlight that strengthening teacher learning communities, collaboration, and interpersonal communication enhances teachers’ personal, professional, pedagogical, and social competencies, enriches creative and innovative teaching methods, and fosters stronger collegial relationships, thereby contributing positively to students’ academic achievement and character development.